Chirality‐Based Biosensors. (14th November 2018) - Ma, Wei; Xu, Liguang; Wang, Libing; Xu, Chuanlai; Kuang, Hua
Abstract: The fabrication of chiral nanostructures gives rise to characteristic chiroptical activity, which can be used for chirality‐based biosensors. Great progress is made in the use of nanoassemblies for the construction of chiral nanoparticle dimers, pyramids, helices, and twisted structures, and their chiroptical activities correlate with diverse structural geometries and enantiomeric configurations. In DNA‐hybridization‐based chiral nanoassemblies, the assembly parameters, such as the components, gaps, multicomponents, and the aftergrowth of metal, can result in multiple bands and enhanced chiroptical effects. Based on known chiral nanostructures, the existing chiral nanoassembly‐based biosensors together with their targets and signal amplification strategies are reviewed. Chirality involves multiple signals, and multitarget biosensors are introduced with newly developed chiral architectures for the accurate and reliable monitoring of biomarkers in living cells. The interactions between chiral nanoarchitectures and biosystems are also highlighted, which are important not only in the chiral dynamic switching of nano‐objects for biomonitoring, but also in manipulating cell growth, proliferation, and adhesion. The future perspectives on chiral fabrication and its use in biosensors are also comprehensively discussed. Abstract : The fabrication of chiral nanoparticle dimers, pyramids, helices, and twisted structures, etc., and their chiroptical activities correlate with diverse structural geometries and enantiomeric configurations. Chirality enables multiple signals‐based multitarget biosensors for the accurate and reliable detection of targets, even in living cells.